Implementation of Individual Counseling Services Using Holland's Theory to Help Ex-Drug Addicts Career Planning - Runi Novita Lestari Sinaga; M. Harwansyah Putra Sinaga (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this research is to help career planning for ex-drug addicts with Holland's theory through individual counselling services. The method used in this research is quantitative with experimental type. This research design is One-Shot Case Study. This research design provides treatment to one group and then observes the results. The population in this study were people with drug addicts in sibolangit cantre rehabilitation totalling 20 people, a sample of 5 people in sibolangit rehabilitation. Sampling was carried out with a purposive sampling model. The results of this study are The implementation of individual counselling services carried out by drug addicts in sibolangit rehabilitation is very helpful for designing career planning for former drug addicts. The conclusion of this study is that the implementation of individual counselling services with Holland's theory to help career planning for former drug addicts using the one shot case study method is less effective to see whether the client's career can be well planned or mature.